Melt elongation flow behaviour of LDPE/LLDPE blends. (February 2015) - Liang, J.Z.; Tan, L.C.; Wang, K.J.; Li, F.J.; Zhang, S.D.
Abstract: The extensional rheological properties of low density polyethylene (LDPE)/linear low density polyethylene (LLDPE) blend melts were measured using a melt spinning technique under temperatures ranging from 160 to 200 °C and die extrusion velocities varying from 9 to 36 mm/s. The results showed that the melt elongation stress decreased with a rise of temperature while it increased with increasing extensional strain rate and the LDPE weight fraction. The dependence of the melt elongation viscosity on temperature roughly obeyed the Arrhenius equation, it increased with increasing extensional strain rate and the LDPE weight fraction when the extensional strain rate was lower than 0.5 s −1, and it reached a maximum when the extensional strain rate was about 0.5 s −1, which can be attributed to the stress hardening effect.